2021
DOI: 10.1177/09514848211010258
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preferences for clinical and managerial leadership roles on the willingness to apply for a medical leadership position: Analysis of gender differences among a sample of German senior physicians

Abstract: Background The hybrid role (clinical and managerial leadership tasks) of physicians in medical leadership positions (MLPs) is a driver of the attractiveness of these positions. The increasing feminization of the medical profession makes gender-related preferences for hybrid roles relevant. Purpose The current study uses the (EPL) career aspirations framework to analyze the (gender-related) effects that efficacy beliefs, motivations, and preferences for clinical leadership and managerial leadership have on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The gender gap widens as women in medicine progress in their academic careers, with studies citing structural and cultural reasons, such as work–life imbalance and non-supportive organizational climates, as contributing factors (Alwazzan & Al-Angari, 2019). Women’s hesitancy to apply for, or accept, promotions has also been suggested as a contributor to the gender leadership disparity, with lower perceptions of self-efficacy and less flexibility in work cited as reasons (Liberatore et al, 2022). Research has also shown that the gender imbalance can differ depending on the medical specialty, with fewer women represented in procedural specialties (with the exception of obstetrics - gynecology) versus nonprocedural and primary care fields (Kennedy et al, 2021; Long et al, 2011; Woodward et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The gender gap widens as women in medicine progress in their academic careers, with studies citing structural and cultural reasons, such as work–life imbalance and non-supportive organizational climates, as contributing factors (Alwazzan & Al-Angari, 2019). Women’s hesitancy to apply for, or accept, promotions has also been suggested as a contributor to the gender leadership disparity, with lower perceptions of self-efficacy and less flexibility in work cited as reasons (Liberatore et al, 2022). Research has also shown that the gender imbalance can differ depending on the medical specialty, with fewer women represented in procedural specialties (with the exception of obstetrics - gynecology) versus nonprocedural and primary care fields (Kennedy et al, 2021; Long et al, 2011; Woodward et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Women currently comprise about half of most graduating medical school classes in the US and they increasingly specialize in obstetrics and gynecology, a field in which they account for 85% of the residents there. 8,9 The growing numbers of women entering both medical and surgical specialties in recent decades [10][11][12] have led to questions about the association between surgeon gender and patient outcomes. A retrospective study reported lower rates of hospital mortality and readmission in hospitalized patients cared for by female compared with male internists.…”
mentioning
confidence: 99%